AB0622 THE EFFICACY OF ADDITIONAL TOCILIZUMAB IN PATIENTS WITH SEVERE POLYMYALGIA RHEUMATICA WHO WERE RESISTANT TO OR INTOLERANT OF CONVENTIONAL THERAPY. (June 2019) - Ueno, Akiko; Hirose, Kei; Hirata, Manami; Yamamura, Yuriko; Yamamura, Masahiro
Abstract : Background: Polymyalgia rheumatica (PMR) is the most common inflammatory disease in the elderly. The 2015 EULAR/ACR recommendations indicate that the management of PMR should be started with glucocorticoids (GCs) and if needed, followed by addition of methotrexate (MTX). The anti-interleukin-6 (IL-6) receptor antibody, tocilizumab (TCZ), has been shown to be effective for PMR. Objectives: To determine the efficacy and safety of TCZ in patients with refractory PMR who were resistant to or intolerant of GCs plus MTX and characterize the clinical profile of patients who need TCZ. Methods: Patients were diagnosed with PMR by the 2012 EULAR/ACR provisional classification criteria and treated according to the 2015 aCR/EULAR recommendations for the management of PMR. TCZ was further added to the patients who were GC plus MTX (GC/MTX)-resistant or -intolerant. The efficacy of treatment was determined by measuring the disease activity with PMR activity score (PMR-AS). We statistically analyzed the differences in clinical indicators between GC-responders, GC/MTX-responders, and GC/MTX-non-responders who need TCZ therapy. Results: Ninety-three patients (53 females and 40 males) were the average of 72.1 ± 9.4 years old, serum CRP 63 ± 42 mg/L, ESR 84 ± 34 mm/hr and blood platelet counts 331 ± 86 ×10 3 /μl, at the first visit, and had been followed up for 25.4±19.6 months. All of them were treated first with prednisolone (PSL) (15.7± 4.3 mg/day). Relapses occurred in 43 patients (46.2%), at the PSL dose of 6.0 ± 5.6 mg/day, after 8.8 ± 6.7 month-GC treatment. GC was increased in 7 patients, and MTX (8.6 ± 2.9 mg/week) was added in 36 patients. Thirteen patients successfully discontinued GC, while 23 patients (24.7%) were resistant to or intolerant of GC/MTX. Ten of 23 patients agreed with TCZ therapy. Before TCZ addition, they were treated with PSL of 6.0 ± 2.2 mg/day plus MTX of 6.0 ± 3.8 mg/week, and serum CRP 9.7 ± 9 mg/L, blood platelet counts 271 ± 32 ×10 3 /μl and PMR-AS 15.5 ±13.5. After 7.3 ± 4.2 month-TCZ treatment, PSL and MTX were reduced to 1.3 ± 1.6 mg/day and 2.2 ± 3.0 mg/week, and CRP, blood platelet counts and PMR-AS decreased to <0.2 mg/L, 191 ± 28 ×10 3 /μl and 5.7 ± 8.3, respectively. GC could be withdrawn in 7 patients, and 4 patients reached drug-free remission. There were significant differences in blood platelet counts and the initial PSL amount between GC/MTX responders and GC/MTX-resistant patients (p<0.05; Mann-Whitney U test). Conclusion: TCZ may provide a therapeutic option for patients with refractory PMR who were resistant to or intolerant of GC/MTX. Our retrospective results suggest that patients with severe PMR, who show thrombocytosis and need high dose GC for initial therapy, may be considered for early induction of TCZ. Disclosure of interests: None declared